Synthetic vulnerability assessment to inform climate-change adaptation along an urbanized coast of Shenzhen, China. (1st February 2020) - Zhang, Yan; Ruckelshaus, Mary; Arkema, Katie K.; Han, Baolong; Lu, Fei; Zheng, Hua; Ouyang, Zhiyun
Abstract: Coastal zones are increasingly threatened by stressors from both climate change and human activities. Vulnerability assessment is central to the implementation of interventions for adapting climate change. However, synthetic vulnerability based on an integrative analysis of ecosystem service and socioeconomic characteristics in urban coastal zones with tightly coupled human-nature interactions is not fully understood. Based on the Coastal Vulnerability model of the InVEST (Integrated Valuation of Environmental Services and Tradeoffs) tool, a holistic framework for assessing coastal vulnerability to multiple hazards (sea level rise, waves and storm surge) was developed by integrating ecological, physical and socioeconomic factors into a single spatial representation and applied to the coast of Shenzhen, China. Based on the levels of biophysical exposure, sensitivity and adaptive capacity of coastal communities, a three-dimensional decision matrix was proposed for planning location-specific interventions. Results show that approximately 15% of the coastline were categorized as having high vulnerability. Spatial vulnerability heterogeneity was found within and across the coastal districts, with Yantian grouped into the most vulnerable district. The biophysical exposure has greater influences on the overall vulnerability than either sensitivity or adaptive capacity. This study highlights the significance of complex interactions between natural ecosystems and socioeconomic conditions in driving vulnerability and suggests that combined natural-based defenses and socioeconomic factors contribute to lower vulnerability. The results can help decision-makers prioritize coastal zones for interventions and identifying adaptive strategies that target drivers of vulnerability. Graphical abstract: Image 1 Highlights: A holistic framework was developed to quantify vulnerability to multi-hazards. Spatial variation in the vulnerability was found within and across the districts. A three-dimensional decision matrix was proposed for location interventions. Biophysical exposure affects vulnerability more than sensitivity and adaptivity.